The Influence of Workload, Work Motivation, and Creativity on Lecturer Performance in the Management Department of UPN Veteran Yogyakarta in the Digital Era - Polonde, Sri Jumiati; Wahyuni, Purbudi; Ambarwati, Sri Dwi Ari (Strata International Journal of Social Issues, 2025)
In response to the challenges of digital transformation in higher education, this study examines the influence of workload, work motivation, and creativity on lecturer performance in the Management Department of Universitas Pembangunan Nasional "Veteran" Yogyakarta. Amid increasing demands on academic staff to fulfill the Tri Dharma of Higher Education—teaching, research, and community service—understanding key performance drivers becomes crucial. Using a quantitative approach, data were collected from all 55 lecturers via a census sampling method. Primary data sources included questionnaires, interviews, and observations, while secondary data were drawn from institutional records. The variables were operationalized using validated indicators and measured on a five-point Likert scale. Validity and reliability tests confirmed acceptable psychometric properties. Multiple linear regression analysis revealed that workload, motivation, and creativity each exert a significant positive effect on lecturer performance (p < 0.05). Notably, the task-related workload indicator received the lowest average score, indicating challenges in balancing academic responsibilities. These findings highlight the importance of institutional interventions such as proportional task distribution, administrative support, and time management training to improve faculty outcomes. The study underscores the necessity for strategic human capital development that supports innovation, engagement, and sustainable academic performance in the digital era.